Small and medium enterprises in the Malaysian economy some lessons learned for SME development in the Philippines - Montes, Nimfa Beatris D. (Journal of Economics, Management & Agricultural Development, 2016)
Small and medium enterprises play a vital role in the agro-industrial development and growth of the Malaysian economy. This paper identifies development issues, major challenges and prospects faced by the Malaysian SMEs entrepreneurs and managers and discusses crucial SMEs development interventions as well as some important lessons learned from their experiences to serve as “guides” to the Philippine government and the local SMEs. Research findings reveal that development issues and challenges include limited adoption of technology, lack of human resources, competition from multinational companies and globalization. In addition, key factors of success were identified: ability to respond quickly to market signals, systematic production and operations management and personal networking. The Malaysian SMEs benefited from the economy’s resilience and competitiveness which are attributed to the continuing fiscal reforms, diversification of the economy and up skilling of capabilities and expertise among others. The country focuses on SMEs strategies such as product innovations in food and beverage manufacturing industry and technology adoption, human capital development, access to financing, market access and infrastructures.